The Effect of Centrifugation on Semen Quality of Peranakan Ettawah Goat's Post Thawing - Indiah Indiah; Sri Wahjuningsih (Jurnal Kedokteran Hewan, 2010)
The aim of the research was to determine the optimum of centrifugation on the quality of Peranakan Ettawah goat's spermatozoa prepared for in vitro fertilization preparation.The research of material was frozen semen ofPeranakan Ettawah goat produced by Artificial Insemination Center in Singosari with minimum post thawing motility in 40%. The method of the research was an experiment method with the four treatment, i.e: 1000 (P1), 1500 (P2), 2000 rpm (P3) of different centrifugation. The variable observes were spermatozoa motility, spermatozoa viability, and abnormal morphology of spermatozoa. Data obtain was analyzed statistically using Completely Randomize Design and continued with Tukey test. The result showed that on the upper layer of each treatment (P1, P2, and P3) obtained 55,72±3,55; 69,55±3,35; and 55,19±2,72% for spermatozoa motility, 62,99±5,87; 73,99±4,36; and 57,39±9,22% for spermatozoa viability, and 7,19±3,64; 8,84±2,65; and 6,40±3,00% for abnormal morphology of spermatozoa, descriptively. While on the lower layer the result showed 55,59±3,99; 68,63±3,88; and57,61±2,20% for spermatozoa motility, 70,05±7,47; 77,44±1,08; and 69,93±11,98% for spermatozoa viability, and 10,36±6,20; 9,55±3,27; and 8,09±2,80% for abnormal morphology of spermatozoa, desciptively. It was concluded that centrifugation in 1500 rpm showed the highest motility and viability on the upper layer and lower layer.